Advertising on social networks - Yuan, Fei (Jihočeská univerzita, 2023)
Exploring companies with active social media accounts increases the number of marketing opportunities. And explore what new, complex and uncontrollable factors social media has introduced to consumer behaviour
Advertising on social networks
Reklama na sociálních sítích
Keywords: active social mediamarketconsumerbehaviour; active social mediamarketconsumerbehaviour